Lead-dependent infective endocarditis and pocket infection – similarities and differences - Polewczyk, Anna; Kędra-Banasik, Agnieszka; Polewczyk, Aneta; Podlaski, Rafał; Janion, Marianna; Kutarski, Andrzej (Medical Studies/Studia Medyczne, 2015)
Introduction : Infectious complications in patients with implanted pacemakers are divided into infections of the generator pocket (PI) and lead-dependent infective endocarditis (LDIE). Aim of the research: Identification of risk factors for developing different types of infections and evaluation of the extent of infectious complications. Material and methods : We compared two groups of patients with infectious complications, who underwent transvenous lead extraction (TLE) in the Reference Centre between March 2006 and July 2013. The groups consisted of 414 patients with LDIE and 205 with PI. We analysed risk factors, clinical manifestations, inflammatory markers, microbiology, and echocardiography results. Results : The coexistence of LDIE and PI was observed in 62.1% patients. There were no significant differences in the presence of host-dependent risk factors. Patients with LDIE significantly more frequently had abrasion of leads (35.1.% vs. 21.0%; p = 0.0001) connected with other procedural risk factors: a larger number of the leads (2.2 vs. 2.0; p = 0.004) lead loops (24.6% vs. 13.2%; p = 0.001), and longer time interval from the last procedure prior to TLE (28.7 vs. 22.6 months; p = 0.005). Fever and pulmonary infections, higher level of erythrocyte sedimentation rate, C-reactive protein, procalcitonin, vegetation presence, and higher pulmonary systolic pressure were also revealed in patients with LDIE. Positive blood and leads culture were observed in 34.5% and 46.4% patients with LDIE. Conclusions: The frequent coexistence of LDIE and PI confirms their common pathogenesis, but the phenomenon of abrasion suggests also another mechanism for the development of LDIE. Intensity of clinical syndromes, high inflammatory parameters, echocardiography, and microbiology findings are helpful in assessment of the extensity of the infection.